Pengaruh Metode Latihan Servis Bawah Bola Voli Dengan Tingkat Kecepatan Servis - Su, Welly; Sugiono; Sukowati, Anton (Jurnal Muara Olahraga, 2024)
The aim of this research was to determine the effect of the volleyball bottom serve training method on the level of service determination of class IX students at SMP Negeri 24 Malaumkarta. This research is descriptive research, the total sample is 25 students. The results of the research show that the highest service level for male and female students in Class IX of SMP Negeri 24 Malaumkarta is in the "sufficient" category with a percentage of 32.0%. Meanwhile, based on the average score obtained at 46.56%, the lower service for male and female students in class IX of SMP Negeri 24 Malaukarta is in the "sufficient" category. The highest lower service for male students in Class IX of SMP Negeri 24 Malaumkarta was in the "sufficient" category, a percentage of 47.0%.  Meanwhile, based on the average score obtained at 40.18%, the lower service of class IX male students at SMP Negeri 24 Malaumkarta was in the sufficient category. The highest lower service for Class IX female students at SMP Negeri 24 Malaumkarta was in the "sufficient" category, a percentage of 50.0% (4 students). Meanwhile, based on the average score obtained at 60.12%, the lower service of class IX male students at SMP Negeri 24 Malaumkarta was in the sufficient category.